Pre- and postsurgical imaging findings of abdominal wall hernias based on the European Hernia Society (EHS) classification (2021)
Abdominal wall hernias are common and can present as technical challenges to surgeons. When large, hernias diminish quality of life. Various classifications of incisional hernias have been proposed; however, there are many terms, sometimes causing confusi